A study on employee’s perception towards training factors and its impact on training effectiveness in Institut Latihan Islam Malaysia (ILIM) Bangi Selangor / Fatin Ruslan - Ruslan, Fatin (2016)
This paper's main objective is to determining the factors that will influence to training effectiveness for an organization. The variables considered are participation of trainees, working environment and training environment. The sample of this study comprises of 80 respondent and 80 questionnaire each of dependent and independent variables on a monthly basis over 4 months period from February 2016 until June 2016.